(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
. In this article, the methodological features of the proverbs used in Shuhrat’s "Golden Rust" were studied and analyzed on a scientific basis. Also, the writer’s ability to use proverbs was widely covered